2017
DOI: 10.3177/jnsv.63.96
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supplementation with Folic Acid on Homocysteine Concentration and Selected Lipoprotein Parameters in Patients with Primary Hypertension

Abstract: SummaryThe aim of the study was the assessment of the impact of supplementation with folic acid on the concentration of homocysteine, total cholesterol (TC), HDL-and LDLcholesterol, triglycerides (TG), apoprotein AI (apoAI) and apoprotein B (apoB) in patients suffering from primary hypertension. The examined group comprised 42 patients suffering from primary hypertension. All examined patients underwent laboratory tests as follows: concentration of homocysteine, folic acid, TC, LDL-cholesterol, HDL-cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Several possible reasons can be proposed to explain the association between the rs1801133 polymorphism and plasma lipid levels. Firstly, the rs1801133 polymorphism may indirectly affect plasma lipid levels through the mediation of homocysteine [ 42 44 ]. Baszczuk et al [ 42 ] reported that a daily administration of 15 mg of folic acid led to a considerable decrease in homocysteine levels, and a substantive increase in HDL-C levels in the patients with primary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible reasons can be proposed to explain the association between the rs1801133 polymorphism and plasma lipid levels. Firstly, the rs1801133 polymorphism may indirectly affect plasma lipid levels through the mediation of homocysteine [ 42 44 ]. Baszczuk et al [ 42 ] reported that a daily administration of 15 mg of folic acid led to a considerable decrease in homocysteine levels, and a substantive increase in HDL-C levels in the patients with primary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…5‐methyltetrahydrofolic acid (5‐methylTHF), the most predominant active metabolite form of FA, involves approximately 82–93% of the total folates in human or animals blood, even has similar level in male and female . Moreover, 5‐methylTHF plays a vital role in the synthesis of purine and thymidylate, and is a key component in the mechanism of homocysteine . As for the pharmacokinetic study, codetermination of free FA and its various metabolites, especially for the 5‐methylTHF, is important to investigate the real plasma concentration–time curve after administration of FA.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Moreover, 5-methylTHF plays a vital role in the synthesis of purine and thymidylate, and is a key component in the mechanism of homocysteine. [8,9] As for the pharmacokinetic study, codetermination of free FA and its various metabolites, especially for the 5-methylTHF, is important to investigate the real plasma concentration-time curve after administration of FA. However, the matrix effect and instability of folates are the main challenges for establishing a special, stable and sensitive method, because of the high fundamental level in blank plasma and easily degraded under common conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory properties of this vitamin have been reported in different pathologies. The administration of folic acid to patients suffering arterial hypertension has been associated with decreased concentrations of homocysteine in serum, and indirectly to decreases of other indicators of inflammation [40]. A trial with obese children and adolescents showed that the treatment with both metformin and folic acid has been associated to decreased insulin resistance and homocysteine levels and that the decrease of the pro-inflamma-tory cytokines TNF-α, IL-8 and IL-6 was related to folic acid administration [41].…”
Section: Vitamins and Inflammationmentioning
confidence: 99%